Program “Sang Penyintas” Berjuang Sembuh dari Covid-19 terhadap Gangguan Psikologis Pasien Terkonfirmasi - Arief Andriyanto; Arif Wicaksono; Catur Prasastia Lukita Dewi (Faletehan Health Journal, 2024)
Many people who were confirmed to have COVID-19 had to undergo self-isolation, causing sufferers to experience fear, anxiety, and panic because this virus had claimed many lives. The occurred psychological disorders must be addressed immediately through programs in accordance with the problems experienced by confirmed patients who were undergoing quarantine. The purpose of this study was to analyze the program of "The Survivor" struggling to recover from COVID-19 against the psychological disorders of confirmed patients. The type of the research was a pre-experimental one-group pre-posttest design. The samples were taken based on a purposive sampling technique of 53 respondents with inclusion criteria, namely confirmed COVID-19 patients without symptoms or mild symptoms and undergoing isolation in quarantine homes. The exclusion criteria were patients with severe symptoms and undergoing hospitalization. The research instrument used the Self-Reporting Questionnaire-29. The analysis used paired t-test statistical test (<0.05). The results obtained p-value of 0.001 which means that there was an effect of the program of "The Survivors" struggling to recover from COVID-19 on the psychological disorders of confirmed patients with the mean before program of 15.89 to be 8.57. Health workers, especially nurses in providing health services to clients, must be more comprehensive and recognize the responses given by clients to be able to prevent ongoing psychological disorders.